2003
DOI: 10.1190/1.1598108
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and AVO responses of a single thin bed

Abstract: The seismic reflection characterizations of a thin layer are important for reservoir geophysics. However, discussions on the reflection for a thin layer are usually restricted to precritical angle incidence. In this work, an exact analytical solution is derived to model the reflection amplitude and amplitude variation with offset (AVO) responses of a single thin bed for arbitrary incident angles. The results show that the influence of an ultra-thin bed is great for opposite-polarity reflections and is small fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 16 publications
5
52
0
3
Order By: Relevance
“…Also, a common measure for the vertical seismic resolution is given by a quarter of the dominant wavelength [53]. As explained in [6], [8] and [54], the CO 2 accumulations within the Utsira sandstone in the Sleipner field can be regarded as thin layers.…”
Section: Finite Thickness Co 2 Accumulations: Frequency Dependent Avamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a common measure for the vertical seismic resolution is given by a quarter of the dominant wavelength [53]. As explained in [6], [8] and [54], the CO 2 accumulations within the Utsira sandstone in the Sleipner field can be regarded as thin layers.…”
Section: Finite Thickness Co 2 Accumulations: Frequency Dependent Avamentioning
confidence: 99%
“…In particular, the curves for the thicknesses h = 5 m and h = 10 m show a periodic behavior; meaning that the different frequency components of a seismic signal are reflected with different amplitudes. To understand this periodicity on a theoretical basis, it is useful to consider the analytical result for the reflectivity of an acoustic layer embedded between two halfspaces, treated in [52] and [53]. From that solution it can be shown that the function R pp (f , θ) has multiple maxima or peaks at frequencies f n max and minima or notches located at frequencies f n min , given respectively by [15] …”
Section: Behavior Of Reflectivity With Saturation Frequency and Thicmentioning
confidence: 99%
“…However, these reflection coefficient formulas are either too complex for application (Brekhovskikh, 1960;Meissner and Meixner, 1969) or only suitable to some extreme hypothetical conditions without considering multiples (Widess, 1973;Chung and Lawton, 1995;Liu and Schmitt, 2003;Pan and Kristopher 2013). In this paper, we initially give the propagator matrix equations for a thin-bed model with displacement functions, different from Brekhovskikh's derivation with displacement potential functions.…”
Section: Introductionmentioning
confidence: 99%
“…Chung and Lawton (1995) extend Widess (1973) study into a thin bed, which has equal amplitudes and identical polarities in the bottom and top interfaces and analyze the influence of different wavelets on thin-bed reflections. Liu and Schmitt (2003) present an acoustic reflectance spectrum formula of a thin bed in the frequency domain and discuss the impact of thickness and Poisson's ratio on thin-bed seismic AVO responses. Pan and Kristopher (2013) compare thin-bed elastic AVO responses with Liu and Schmitt's (2003) acoustic AVO responses, and they investigate the influence of quality factor Q to examine attenuation effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation